PENYULUHAN TENTANG BEBAN KERJA DAN PENGELOLAAN STRESS KERJA PERAWAT DI KLINIK TERATAI MEDICAL CENTRE - Herlina J EL Matury; Hengky Frengky Manullang; Usaha Satria Pratama Tarigan; Evalina Manurung (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
ABSTRACT Nurses are medical personnel who provide medical services to the community to support the health and recovery of patients. every hospital always needs a nurse and they have a high responsibility for the tasks they do and are able to show good work performance to the relevant agencies, nurses must also always maintain their attitude in front of patients, superiors and with fellow nurses so that relationships which is run running as desired with comprehensive nursing care is also a job that has a high level of stress, and a workload for nurses. Workload can be interpreted as an activity that must be completed by a person or group of people during a certain period of time under normal circumstances. In measuring the level of workload felt by a person, the proportion of work time charged to nurses in completing their work must be balanced. The problem of workload and work stress affect the level burnout experienced by a person. Job stress has a relationship with the increasing demands of the workload. Prolonged work stress with unstable emotional conditions will indirectly trigger a decrease in work competitiveness. All types of stress are basically caused by a person's lack of understanding of each other's capabilities. When someone does not know their capabilities, this triggers the occurrence of symptoms related to work stress. Work stress is associated with accidents, workplace violence, organizational strain in the form of absenteeism, decreased work performance, increased injury rates and employee turnover. Nursing is a profession that has a high risk of being affected by work stress.